IMPROVING STUDENTS’ VOCABULARY THROUGH PELMANISM GAME - Zia, Halida; Rufinus, Albert; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The aim of this research was to find out how well the use of Pelmanism Game in improving students? vocabulary. This research used Classroom Action Research. There were two problems encountered. First, most of the students did not know the meaning of English words. Second, most of the students mispronounced some English words. This research consisted of two cycles. The tools of data collecting were observation checklist, field note, and test. This research was implemented to 39 seventh grade students of SMP LKIA Pontianak in academic year 2014/2015. The students? responses showed that they were interested in learning vocabulary through pelmanism game. It can be seen through the students? mean score in the first cycle that was 78.7 to 90.1 in the second cycle. It can be concluded that the students? vocabulary taught by using pelmanism game improved. Keywords: Vocabulary, Game, Pelmanism Game Abstrak: Tujuan dari penelitian ini adalah menemukan bagaimana penggunaan permainan pelmanism dalam meningkatkan kosakata siswa. Penelitian yang digunakan yaitu Penelitian Tindakan Kelas. Ada dua masalah yang ditemukan. Pertama, banyak siswa yang tidak mengetahui arti dari kata-kata dalam Bahasa Inggris. Kedua, banyak siswa yang salah dalam mengucapkan kata-kata dalam Bahasa Inggris. Penelitian ini terdiri dari 2 siklus. Alat yang digunakan dalam pengumpulan data adalah lembar pengamatan ceklis, catatan lapangan, dan tes. Penelitian ini dilakukan kepada 39 siswa kelas 7 SMP LKIA Pontianak di tahun ajaran 2014/2015. Respon siswa menunjukkan bahwa mereka tertarik belajar Bahasa Inggris dengan permainan pelmanism. Hal ini bisa dilihat dari nilai rata-rata siswa pada siklus pertama yaitu 78,7 menjadi 90,1 pada siklus kedua. Bisa disimpulkan bahwa perbendaharaan kosakata siswa yang diajarkan melalui permainan pelmanism meningkat. Kata kunci: Kosakata, Permainan, Permainan Pelmanism